Neuroprotective effects of exosome therapy in Parkinson’s disease: a systematic review - Naik, Vijay; Pereira, Myla; Nayak, Chitralekha; Sayed, Farook (International Journal of Research in Medical Sciences, 2025)
Parkinson’s disease (PD) is a progressive neurodegenerative disorder characterized by the loss of dopaminergic neurons. Current treatments primarily address symptoms but fail to halt disease progression. Exosome-based therapies have emerged as a promising neuroprotective strategy due to their ability to cross the blood-brain barrier and deliver bioactive molecules. This systematic review and meta-analysis aim to evaluate the neuroprotective potential of exosome therapy in PD by synthesizing data from preclinical studies. A systematic literature search was conducted in PubMed, Embase, Web of Science and Scopus. Studies were included if they examined exosome therapy in PD models, evaluated neuroprotective effects and provided clear methodological details. Data extraction focused on exosome sources, experimental models, therapeutic mechanisms and outcomes. Risk of bias was assessed using the SYRCLE tool. Twelve preclinical studies met the inclusion criteria. Exosomes derived from mesenchymal stem cells demonstrated significant neuroprotective effects, including reduced neuronal apoptosis, restoration of autophagy, inhibition of neuroinflammation and enhanced dopaminergic neuron survival. Key mechanisms involved the modulation of signalling pathways (PI3K/AKT, NOX4-ROS-Nrf2 and TLR4/NF-κB/NLRP3). Despite these promising findings, variability in exosome isolation, administration routes and study designs was noted. Exosome therapy exhibits strong neuroprotective potential in preclinical PD models. However, standardized protocols, dose optimization and rigorous clinical trials are essential for translating these findings into viable treatments.